Impeding effect of bubbles on metal transfer in underwater wet FCAW. (September 2019) - Yang, Qingyuan; Han, Yanfei; Jia, Chuanbao; Wu, Junfei; Dong, Shengfa; Wu, Chuansong
Graphical abstract: Highlights: Reasonable optical path is designed for synchronous visual detection of droplet transition and bubble behavior. The reasons for large droplet size and low transition frequency under low arc voltage conditions are explained from the point of view that bubbles impede droplet transition. Bubble behavior is an important reason for droplet floating, deviation and spatter formation. Abstract: Aiming at the complicated physical process of underwater wet welding, two background light sources, laser and dysprosium lamp, are combined with high-speed camera to realize synchronous visual sensing of metal transfer, bubble evolution and arc behaviors. The dynamic changes of droplets and bubbles under different arc voltage conditions are investigated. Their interaction relationships are described in detail. From the perspective of the bubble impeding the metal transfer, the reason for the large droplet diameter and low transfer frequency under low arc voltage conditions is analyzed. The gas flow drag force ( F L ) is the largest at the neck of the bubble separation stage, which greatly affects the stability of the metal transfer process. When the droplet is located above the neck, it is easy to be carried away by separated bubbles to form a spatter. At the same time, the bubbles rising away from the axis of the wire can easily cause the droplet to deviate from the wire.